Model STAD Berbantuan Peta Untuk Meningkatkan Kemampuan Berpikir Spasial Peserta Didik Pada Pembelajaran Geografi Kelas X-7 Di SMAN 1 Telaga - Halifa S. Soyang; Rakhmat Jaya Lahay; Moch. Rio Pambudi (Universitas Negeri Gorontalo, 2026)
This study aims to determine the implementation of the STAD Cooperative learning model in improving students' spatial thinking skills in class X-7 SMAN 1 Telaga through the application of the Student Teams Achievement Division (STAD) cooperative learning model. The research method used is Classroom Action Research (CAR). The study was conducted in two cycles, each cycle consisting of planning, action implementation, observation, and reflection. The subjects of this study were 38 students of class X-7 SMAN 1 TELAGA. This study was conducted collaboratively between researchers and Geography subject teachers. Data collection techniques used in this study include tests and observations. Data collection instruments used were tests and observation sheets. The results of this study indicate that the application of the STAD type cooperative model can improve students' spatial thinking skills. The increase can be seen from the average score from pre-action to cycle II. In the pre-action, the average student scored 42.68, then increased to 63.31 in cycle I and increased again to 87.31 in cycle II. The increase in the average score from cycle I to cycle II was 4.05, while the average class score from pre-action to cycle II was 9.7. Because it had reached the completion criteria, namely 89% of students obtained a score above or equal to the KKM (70), this research was said to be successful.